Implementation of Quality Management for Food Combining on Startup Business PT. Beras Jagung Nusantara - Abu Naim; Tantri Yanuar R. Syah; Semerdanta Pusaka; Dadan Ramdhani (Journal of Multidisciplinary Academic, 2019)
PT. Beras Jagung Nusantara. This research aims to make the business activities to be conducted are in accordance with the plan; and to be able to find out the company's current position, the direction of the company's goals and how to achieve the target market that the company wants to achieve. This research is also influenced by the strategy that we choose. The companies must be aware due to the amount of demand for the products which are being made, by looking at market conditions and corporate strategy. The results shows the company are trying to offer Food Combining products, which are different from the products that are already on the market; both in terms of taste, quality and more affordable prices. The company's operational activities are very possible to be conducted, therefore the company can offer more competitive prices compared to the imported products that have already entered the market. This Type One Waste activity must be eliminated, or at least reduced. Type One Waste is often referred to as Incidental Activity or Incidental Work, which is a non-value adding work or activity. The next type of waste is Type Two Waste, which is an activity that does not create added value and can be eliminated immediately. For example, produce product defects or make mistakes (errors). Type Two Waste is often referred to only as 'waste', because it is wasteful and must be identified and eliminated at once. The relationship between Sigma and DPMO of PT. Beras Jagung Nusantara began in February.